SEJARAH PEMIKIRAN SUMBER AJARAN ISLAM DAN PENDIDIKAN ISLAM - Dzat MR, Ahmad Faizal; Erliyanto, Mohammad (CV. Jendela Gagasan, 2024)
The history of thought in the field of Islamic sources, which includes the Qur'an, Hadith, Ijma', and Qiyas, plays an important role in the development of Islamic law and thought throughout time. Along with social, political, and economic changes, the relevance of these sources in facing the challenges of the times is increasingly important to understand. This research aims to examine the contribution of the history of thought in developing the Islamic legal system and answering the challenges of modern times. The method used in this research is a qualitative approach with the type of library research, which relies on literature studies from various primary and secondary sources. The results show that the process of the Qur'an and Hadith codification in a historical perspective shows how the Qur'anic revelation was systematically revealed and how the Hadith were collected to maintain the authenticity of the source of Islamic teachings, so that they become the main guidelines in determining Islamic law. In dealing with legal issues that are not explicitly explained in the basic texts, the scholars then developed the Ijma' and Qiyas methods as ijtihad methods to find contextual legal solutions. Ijma' as a consensus of scholars and Qiyas as a legal analogy play an important role in expanding the scope of Islamic law beyond the classical texts, and provide a basis for establishing law in new situations. Over time, Islamic legal thought underwent significant development, especially in the classical period (8th to 19th centuries), where it was influenced by social dynamics, politics, and evolving intellectual traditions, as well as debates between madhhabs that sought to keep the law in line with the context of the times. In this case, the methodology developed by the classical scholars not only helped to answer fiqh muamalah and family law issues, but also provided solutions to the social and cultural challenges faced by Muslims. Thus, although the challenges of the times continue to grow, the history of Islamic thought shows that the basic principles of Islamic teachings remain relevant and able to provide guidance in answering various increasingly complex social, economic and political problems, without sacrificing fundamental religious values.